(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
In this study, researchers in Rivers State, Nigeria, looked at NIMASA, the country’s maritime administrative and safety agency, to see how much of an impact the cabotage legislation has on the ongoing development of indigenous human capital. The study included two goals and two research questions. Following this, the research included the Human Development theory into its theoretical framework to elucidate the ever-changing character of Cabotage legislation as well as indigenous peoples’ efforts to build sustainable human capability. This study used a descriptive survey research strategy. The study’s population was 197, and the sample size that was ultimately employed was 181, using the census sampling approach. We used questionnaires to gather data. We used basic statistical tools like percentages, charts, means, and standard deviations to examine the data. Research in Rivers State, Nigeria, found that indigenous human capital is better used in the maritime industry, which in turn has increased the number of chances for Nigerians to have a say in Nigerian maritime affairs. The study recommended among others that since the level of implementation is not yet satisfactory, Nigerian government should carry out stricter cabotage policy that could limit waivers to foreign vessels, as this would ensure that Nigerians take full control of their maritime activities, to enhance sustainability